Elevated Serum Lactate Dehydrogenase Predicts Unfavorable Outcomes After rt-PA Thrombolysis in Ischemic Stroke Patients - Jin, Huijuan; Bi, Rentang; Hu, Jichuan; Xu, Da; Su, Ying; Huang, Ming; Peng, Qiwei; Li, Zhifang; Chen, Shengcai; Hu, Bo (Frontiers in Neurology, 2022)
Background and Purpose Currently, acute ischemic stroke (AIS) is one of the most common and serious diseases in the world and is associated with very high mortality and morbidity even after thrombolysis therapy. This study aims to research the relationship between lactic dehydrogenase (LDH) and prognosis in AIS patients treated with intravenous rtPA. Method This study (a Multicenter Clinical Trial of Revascularization Treatment for Acute Ischemic Stroke, TRAIS) included 527 AIS patients in 5 cooperative medical institutions in China from January 2018 to February 2021. The primary outcome was major disability and death within 3 months (mRS score of 3–6), and the secondary outcomes were early neurological improvement (ENI), early neurological deterioration (END), moderate-severe cerebral edema (CE), and symptomatic intracranial hemorrhage (sICH). Results The mean age of the 527 patients was 65.6 ± 11.7 years, and the median baseline NIHSS score was 4 (interquartile range, 2–7). The median serum LDH level was 184 U/L (interquartile range, 163–212 U/L). In total, 287 (54.5%) patients acquired ENI, 68 (13.0%) patients suffered END, 53 (12.1%) patients were observed with moderate-severe CE, and 28 (6.2%) patients showed sICH. Within 3 months, 127 (25.15%) patients experienced the primary outcome and 42 (8.3%) patients died. Serum LDH levels before thrombolysis showed an independent association with the risk of primary outcome [adjusted odds ratio, 3.787; (95% CI, 1.525–9.404); P = 0.014]. When log-transformed LDH increased each standard deviation, the risk of primary outcome was raised by 80.1% (95% CI, 28.9–251.7%). A positive linear dependence between the risk of primary outcome and serum LDH levels (P of linearity = 0.0248, P of non-linearity = 0.8284) was shown in multivariable-adjusted spline regression models. Pre-thrombolysis LDH quartile also provided a conventional risk model and significant improvement of the prediction for clinical outcomes, with a net reclassification improvement index (NRI) = 41.86% (P < 0.001) and integrated discrimination improvement (IDI) = 4.68% (P < 0.001). Conclusions Elevated serum LDH levels predicted unfavorable clinical outcomes after intravenous thrombolysis in AIS patients.